2020
DOI: 10.3389/fphar.2020.00346
|View full text |Cite
|
Sign up to set email alerts
|

Danhong Injection Protects Hemorrhagic Brain by Increasing Peroxiredoxin 1 in Aged Rats

Abstract: Intracerebral hemorrhage (ICH) is a severe cerebrovascular disease with a high incidence, mortality and disability rate. Danhong injection (DHI) is beneficial for ischemic stroke, but is prohibited for ICH due to risk of bleeding. The present study aims to explore the potential therapeutic time window and molecular mechanism of DHI in a collagenase-induced ICH model in aged rats. DHI administration after ICH could significantly improve body weight and neurological deficits, and reduce the hematoma volume and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Thus, baicalein can potentially be used to treat ICH and related brain injuries [ 101 ]. Danhong—a traditional Chinese medicine extracted from 2 herbs (Salviae miltiorrhiza Bunge (Danshen, China) and Carthamus tinctorius L (Honghua, China))—contains flavonoids and phenolic compounds and was reported to increase the expression of peroxiredoxin (Prx) 1 in astrocytes, thereby preventing severe brain injury following ICH in aged rats [ 102 ]. In addition, carnosine [ 103 ], COA-Cl (a novel synthesized nucleoside analog) [ 104 ], AE1-259-01 EP2 receptor agonists [ 105 ], green tea and red tea [ 57 ], protocatechuic acid (PCA) [ 106 ], nebivolol [ 107 ], 14Adiponectin (APN) [ 108 ], metformin [ 109 ], C1q/tumor necrosis factor-related protein 3 (CTRPs) [ 15 ], gastrodin [ 110 ], Naringin (NGN) [ 111 ], and Parthenolide (PN) [ 112 ] are all effective antioxidants in ICH animal models.…”
Section: Therapeutic Strategies Targeting Os Following Ich (Supplementioning
confidence: 99%
“…Thus, baicalein can potentially be used to treat ICH and related brain injuries [ 101 ]. Danhong—a traditional Chinese medicine extracted from 2 herbs (Salviae miltiorrhiza Bunge (Danshen, China) and Carthamus tinctorius L (Honghua, China))—contains flavonoids and phenolic compounds and was reported to increase the expression of peroxiredoxin (Prx) 1 in astrocytes, thereby preventing severe brain injury following ICH in aged rats [ 102 ]. In addition, carnosine [ 103 ], COA-Cl (a novel synthesized nucleoside analog) [ 104 ], AE1-259-01 EP2 receptor agonists [ 105 ], green tea and red tea [ 57 ], protocatechuic acid (PCA) [ 106 ], nebivolol [ 107 ], 14Adiponectin (APN) [ 108 ], metformin [ 109 ], C1q/tumor necrosis factor-related protein 3 (CTRPs) [ 15 ], gastrodin [ 110 ], Naringin (NGN) [ 111 ], and Parthenolide (PN) [ 112 ] are all effective antioxidants in ICH animal models.…”
Section: Therapeutic Strategies Targeting Os Following Ich (Supplementioning
confidence: 99%
“…Numerous studies have found DHI has protective effects on the central nervous system, such as in ischemia-reperfusion injury model rats DHI can pass to protect the blood-brain barrier and reversal neutrophils in ltrating to play a protective role. For example, DHI protects the blood-brain barrier and reverse neutrophil in ltration in rat models of cerebral ischemia-reperfusion injury [30], and DHI increases the expression of astrocytes Peroxiredoxin 1 in subarachnoid hemorrhage models and reduces the expression of in ammatory factors such as tumor necrosis factor (TNF) and interleukin-1 (IL-1), thereby reducing hematoma volume and brain water content and improving neurological de cits [18].…”
Section: Discussionmentioning
confidence: 99%
“…They are widely used in clinical practice and numerous clinical observations have con rmed that coronary heart disease, heart failure, stroke, cerebral hemorrhage, vertebrobasilar artery ischemic vertigo, and diabetic peripheral neuropathy receiving DHI therapy got favorable outcome [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Since DH launch in 2002, it has been widely used to prevent and treat ACS ( Yao et al, 2011 ). The main active ingredients of DH are flavonoids and phenolic compounds, for example, danshensu, salvianolic acid B, protocatechuic aldehyde, tanshinone IIA, rosmarinic acid and hydroxysafflor yellow A ( Xie et al, 2014 ; Wang et al, 2020 ). In addition, previous pharmacological studies have demonstrated that DH have the effects of antioxidant, anti-inflammatory, vasodilation and protect cardiac muscle due to its main pharmacological active components ( Wan et al, 2011 ; Jiang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%